Analysis of Early Childhood Fine Motor Skills Through the Application of Learning Media - Resi Rosalianisa; Budi Purwoko; Nurchayati Nurchayati (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The learning media is one of the methods needed in the learning process when students are in class, especially for developing fine motor skills. Fine motor skills are fine motor skills that involve finely coordinated movements. This research was conducted to describe and analyze the implementation of the learning media to develop and stimulate the development of children's fine motor skills. The novelty of the research is learning media to improve fine motor skills in early childhood. This study aims to describe fine motor skills in early childhood through learning media. Method: This research method is a literature study or literature review with a qualitative approach that is carried out by collecting data or based on scientific writing, which combines research with existing literature to solve existing problems—collecting data on library materials by reading and storing and managing research materials and concluding research materials. Results: Based on an analysis of 30 learning articles using learning media shows that developing fine motor skills in early childhood requires learning activities using learning media to support and support the learning process. In addition, when the learning process uses learning media, children become interested, enthusiastic, and excited because learning activities become fun. Novelty: The novelty of the research is learning media to improve fine motor skills in early childhood.